Entrepreneurial Orientation and Export Performance among Malaysian Small and Medium-Sized Exporters: The Mediating Role of International Opportunity Recognition - Faiz, Masnan (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis (UniMAP), 2019)
Link to publisher's homepage at http://ijbt.unimap.edu.my